2013
DOI: 10.1111/geb.12136
|View full text |Cite
|
Sign up to set email alerts
|

Unsupported inferences of high‐severity fire in historical dry forests of the western United States: response to Williams and Baker

Abstract: Reconstructions of dry western US forests in the late 19th century in Arizona, Colorado and Oregon based on General Land Office records were used by Williams & Baker (2012; Global Ecology and Biogeography, 21, 1042-1052; hereafter W&B) to infer past fire regimes with substantial moderate and high-severity burning. The authors concluded that present-day large, high-severity fires are not distinguishable from historical patterns. We present evidence of important errors in their study. First, the use of tree si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 48 publications
1
59
1
Order By: Relevance
“…Their inferences are based on conclusions drawn from vegetation reconstructions using General Land Office (GLO) or federal Forest Inventory and Analysis (FIA) data. While these data are useful for general descriptions and tabulations of historical vegetation conditions, they are unsuited to making spatially accurate inferences as to local historical vegetation conditions, or for inferring disturbance regimes from size distributions of trees (Fulé et al, 2014;Stevens et al, in press). While needs vary both regionally and locally, we strongly disagree with the contention that ecological restoration is unnecessary in MSForests of the Inland Pacific West, as do a host of authors throughout the Inland West: Barth et al (2015), Collins et al (2011aCollins et al ( , 2015, Gaines et al (2010aGaines et al ( , 2010b, Spies et al (2010), Hessburg and Agee (2003), Hessburg et al (1999aHessburg et al ( , 1999bHessburg et al ( , 2000aHessburg et al ( , 2005Hessburg et al ( , 2013Hessburg et al ( , 2015, Taylor (2004), Stephens et al (2009Stephens et al ( , 2010Stephens et al ( , 2015, Moghaddas et al (2010), Scholl and Taylor (2010), Hagmann et al (2013Hagmann et al ( , 2014, Merschel et al (2014), Perry et al (2011), Harris and Taylor (2015), and Franklin and Johnson (2012).…”
Section: Management Challenges In Msforestsmentioning
confidence: 99%
“…Their inferences are based on conclusions drawn from vegetation reconstructions using General Land Office (GLO) or federal Forest Inventory and Analysis (FIA) data. While these data are useful for general descriptions and tabulations of historical vegetation conditions, they are unsuited to making spatially accurate inferences as to local historical vegetation conditions, or for inferring disturbance regimes from size distributions of trees (Fulé et al, 2014;Stevens et al, in press). While needs vary both regionally and locally, we strongly disagree with the contention that ecological restoration is unnecessary in MSForests of the Inland Pacific West, as do a host of authors throughout the Inland West: Barth et al (2015), Collins et al (2011aCollins et al ( , 2015, Gaines et al (2010aGaines et al ( , 2010b, Spies et al (2010), Hessburg and Agee (2003), Hessburg et al (1999aHessburg et al ( , 1999bHessburg et al ( , 2000aHessburg et al ( , 2005Hessburg et al ( , 2013Hessburg et al ( , 2015, Taylor (2004), Stephens et al (2009Stephens et al ( , 2010Stephens et al ( , 2015, Moghaddas et al (2010), Scholl and Taylor (2010), Hagmann et al (2013Hagmann et al ( , 2014, Merschel et al (2014), Perry et al (2011), Harris and Taylor (2015), and Franklin and Johnson (2012).…”
Section: Management Challenges In Msforestsmentioning
confidence: 99%
“…Large trees shade their smaller neighbors, dominate the rooting zone, and harbor large populations of pathogens, herbivores and mutualists (e.g., mycorrhizae) (Laliberte et al 2015). Individual trees often live for centuries, and although age-size relationships can be highly variable (Youngblood et al 2004, Fulé et al 2014, larger individuals usually tend to be older than smaller conspecifics in forests that are in stable conditions (Leak 1985). Thus, we used the size of focal trees (diameter at 1.3 m above ground, DBH) as an integrator of the strength and duration of interactions with neighbors and asked whether the phylogenetic composition of neighbors surrounding focal trees shifted with focal tree size.…”
Section: Accepted Ar Ticlementioning
confidence: 99%
“…Fulé et al (2014) suggested some of our GLO methods were invalid. In response, we explained that our methods were extensively tested, validated, and shown to be accurate, and we added new corroboration .…”
Section: Study Areamentioning
confidence: 99%
“…Some are concerned that recent high-severity patch sizes are uncharacteristically large and damaging in dry western forests (Stephens et al 2013, Fulé et al 2014). However, these articles surprisingly presented no patch-size data (Williams and Baker 2014).…”
Section: Management Implicationsmentioning
confidence: 99%